Modified Polyadenylation-Based RT-qPCR Increases Selectivity of Amplification of 3′-MicroRNA Isoforms - Nejad, Charlotte; Pépin, Geneviève; Behlke, Mark A.; Gantier, Michael P. (Frontiers in Genetics, 2018)
microRNA (miRNA) detection by reverse transcription (RT) quantitative real-time PCR (RT-qPCR) is the most popular method currently used to measure miRNA expression. Although the majority of miRNA families are constituted of several 3’-end length variants (“isomiRs”), little attention has been paid to their differential detection by RT-qPCR. However, recent evidence indicates that 3’-end miRNA isoforms can exhibit 3’-length specific regulatory functions, underlining the need to develop strategies to differentiate 3’-isomiRs by RT-qPCR approaches. We demonstrate here that polyadenylation-based RT-qPCR strategies targeted to 20-21 nt isoforms amplify entire miRNA families, but that primers targeted to >22 nt isoforms were specific to >21 nt isoforms. Based on this observation, we developed a simple method to increase selectivity of polyadenylation-based RT-qPCR assays towards shorter isoforms, and demonstrate its capacity to help distinguish short RNAs from longer ones, using synthetic RNAs and biological samples with altered isomiR stoichiometry. Our approach can be adapted to many polyadenylation-based RT-qPCR technologies already exiting, providing a convenient way to distinguish long and short 3’-isomiRs.